"Why, what and whither of the public sector enterprise / edited by Malcolm S. Adiseshiah" (New Delhi, 1986)
The Public Sector has now become of topical interest as the major source of financing the Seventh Plan, because the fiscal sources are just able to cover the non-plan expenditures of the governments of the Union and the states. Bearing this in mind, the Economic Affairs Group of the India International Centre, in collaboration with SCOPE, organised in the first half of 1985, a series of panel discussions on the public sector, culminating in a seminar.
Keywords: Public enterprises